Masters of sketching - Cording, Debbie (Worcester, United Kingdom : 3Dtotal Publishing, 2016)
Sketching has been used by generations of artists as a way of quickly capturing something they see, working out concepts, or planning a final composition. They are generally not used as a final rendered image. We have gathered together twenty Master sketchers who have taken sketching to the next level. They will take you, step-by-step, through their process, sharing their creative insight along the way. So, whether you want to improve your drawing or you are just starting out, Masters of Sketching is an outstanding collection of useful tutorials and inspiring images.
-- Patrick Ballesteros -- Paride Bertolin -- Mike Corriero -- Tom Fox -- Eliza Ivanova -- Zoe Keller -- Kikyz1313 -- Abigail Larson -- Sean Layh -- Larry MacDougall -- Jeremy Mann -- Christina Mrozik -- Jim Pavelec -- Bobby Rebholz -- Kirill Semenov -- Annie Stegg Gerard -- Ania Tomicka -- Eduardo Vieira -- Colie Wertz -- Sam Wolfe Connelly.
"Warning: this book contains nudity" -- Back cover.
Keywords: Drawing -- Technique